The local limit theorem of large deviations for multiplicative functions - Rimantas Skrabutėnas (Lietuvos Matematikos Rinkinys)
In the present paper we continue investigation of the local distribution of multiplicative arithmetic functions from the class M(G). A local theorem of large deviations is obtained.